Phosphonite ligand design for nickel-catalyzed 2-methyl-3-butenenitrile isomerization and styrene hydrocyanation - Tauchert, Michael E.; Kaiser, Thilo Robert; Göthlich, Alexander P. V.; Rominger, Frank; Warth, Daniel C. M.; Hofmann, Peter (ChemCatChem, 2010)
The synthesis of a series of novel chelating bisphosphonite ligands with a bridged dihydroanthracene scaffold is described. First-generation derivatives showed a strong tendency for the formation of catalytically inactive Ni0 bis-chelate complexes. The solid state structures of these complexes allowed the design of tailor-made second-generation ligands for nickel-catalyzed 2-methyl-3-butenenitrile isomerization with exceptionally high activity. The second-generation catalyst also showed good catalytic performance in the hydrocyanation of styrene.
Dedicated to Prof. Dr. Günther Wilke on the occasion of his 85th birthday
Gesehen am 15.09.2023